Microbiological and Sensory Quality of Milk on the Domestic Market - Piotrowska Anna; Świderski Franciszek; Kostyra Eliza; Żebrowska-Krasuska Małgorzata; Sadowska Anna (Polish Journal of Food and Nutrition Sciences)
The evaluation of the microbiological and sensory quality of 30 assortments of market milk was the objective of the presented research. The study also compared the sensory profile of selected samples of milk differing in preservation method. Microbiological tests included determination of the presence and number of Enterobacteriaceae and the total number of microorganisms. Sensory characteristics of all the milk samples was performed by scaling method (5-points scale). Selected samples of milk were additionally assessed by means of profile method. Microbiological tests showed satisfactory microbiological purity of milk, which indicates the effectiveness of the heat treatment and the lack of secondary contamination. Regardless of the preservation method, all the evaluated milk samples were characterised by a high sensory quality (4.25-5 points). There were no changes in smell and taste, resulting from the development of undesirable microflora. The tested samples of milk differing in the preservation method (sterilisation, pasteurisation at high temperature and subjected to microfiltration and low pasteurisation) varied in the sensory profile. Milk pasteurised at high temperature was characterised by the most harmonised overall quality.